Capacity of Local Governments in Implementing the National Agenda: A Case Study of the Implementation of The RPJMN of North Sumatra Province - Pin Pin; Khairuddin Tampubolon; Gunawan Undang (Khazanah Sosial, 2026)
This study aims to analyze in-depth the capacity of local governments to implement the national agenda through the implementation of the National Medium-Term Development Plan (RPJMN) in North Sumatra Province. Local government capacity is a key aspect in determining the effectiveness of national policy implementation at the local level, as regions play the primary role in realizing development targets set by the central government. The research approach used a qualitative method with a case study design, which allows researchers to understand the phenomenon comprehensively and contextually. Data were collected through in-depth interviews with officials from the Regional Development Planning Agency (Bappeda), organizational bureaus, and several related regional agencies. In addition, an analysis of regional planning documents, performance reports, and the results of monitoring and evaluation of the RPJMN implementation was conducted. The results of the study indicate that the capacity of local governments to implement the RPJMN in North Sumatra Province still faces structural and cultural challenges. The main challenges include limited competent human resources in the planning field, weak coordination across sectors and levels of government, and limitations in the use of data and information technology for evidence-based planning. However, there are also indications of increasing institutional capacity through apparatus training programs, the implementation of regional development information systems, and strengthening coordination mechanisms between the central and regional governments. The North Sumatra Provincial Government has also attempted to harmonize the RPJMD and RPJMN to ensure that regional development policies align with the national development direction. These findings confirm that the successful implementation of the RPJMN is determined not only by administrative and technocratic factors, but also by the adaptive and collaborative capabilities of local governments in responding to central government policies. Local government capacity must be understood as a combination of human resource competency, institutional capacity, and the ability to build networks with various stakeholders. This research provides a theoretical contribution to the study of public administration, particularly in the context of decentralization and the implementation of national policies in the regions. Practically, the results of this study recommend the need for a strategy to strengthen institutional capacity based on effective, participatory, and adaptive governance to change. Thus, North Sumatra Province can serve as an example of a more synchronized, measurable, and sustainable implementation of the national agenda.